Coexistence of eumycetoma and tuberculosis in a same lesion in right thigh in an adult: a rare case report - Subramaniam, Rajesh; Venkat, Shruthikamal; Sattar, Reshma (International Surgery Journal, 2016)
Eumycetoma is an uncommon infection in adults, especially as a co-infection with extra pulmonary tuberculosis. We report a unique case of Co-existence of Eumycetoma and tuberculosis in a same lesion in an adult from a known endemic area of Tamilnadu, India which posed a diagnostic and therapeutic challenge.